2017
DOI: 10.20547/jms.2014.1704106
|View full text |Cite
|
Sign up to set email alerts
|

Co-integration of Sukuk and Bond Yields - Evidence from Globally Placed Sukuk

Abstract: The study addresses the question "How do the financial markets perceive and price internationally issued Islamic bonds?" It is examined by empirically testing for the evidence of co-integration of sukuk yields with the US Treasury yields using Vector Error Correction (VEC) models. Our results indicate that the sukuk yields are highly co-integrated with the US Treasury yields in long-term relationships. The short-term dynamics of the sukuk yields with the interest rate series is, however, complex showing bi-dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The linear regression analysis approach has been followed by Koenker and d'Orey (1987), with the intention to quantify the errors of parameters of given Equation (1) after incorporating the heteroscedasticity effects in quantile regression deterministic technique through bootstrapping function (Buchinsky 1995). The present quantile regression approach has been endorsed by (Uppal and Mangla 2017).…”
Section: Empirical Model Specificationmentioning
confidence: 99%
“…The linear regression analysis approach has been followed by Koenker and d'Orey (1987), with the intention to quantify the errors of parameters of given Equation (1) after incorporating the heteroscedasticity effects in quantile regression deterministic technique through bootstrapping function (Buchinsky 1995). The present quantile regression approach has been endorsed by (Uppal and Mangla 2017).…”
Section: Empirical Model Specificationmentioning
confidence: 99%
“…Authors suggested empowering the employees within certain limits so that the notion of job autonomy in association with high-quality LMX relationship could possibly accelerate the organizational learning and employee creativity. Uppal and Mangla (2017) investigated the performance of internationally issued Islamic bonds (Sukuk) in paper six. From the results, it was inferred that international markets are viewing and pricing the Sukuk in a manner similar to that for conventional bonds.…”
mentioning
confidence: 99%